Hak Guna Bangunan di Atas Air: Legalitas dan Regulasi Serta Tantangan dalam Implementasi - Martin, Carmelie Clara (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
The Right to Build (Hak Guna Bangunan/HGB) is one of the land rights recognized under Indonesia’s agrarian legal system. However, its applicability over water areas remains legally ambiguous. This study examines the legality of HGB over water, the regulatory gaps, and the challenges in its implementation. A normative juridical approach is used, involving the analysis of legislation and a case study of a reclamation project in Jakarta’s coastal area. The findings indicate that the absence of explicit legal provisions regarding HGB over water creates uncertainty for investors, poses risks of conflict with coastal communities, and threatens marine environmental sustainability. Therefore, regulatory reform and policy harmonization between agrarian and maritime sectors are essential to ensure legal certainty and promote sustainable investment.